Shadows of pecan hollow eaudiobook A novel. - Frost, Caroline (HarperAudio, 2022)
Winner of the Crook's Corner Book Prize, finalist for the Golden Poppy Award, and longlisted for the Center for Fiction First Novel Prize ""This immersive, full-bodied novel will keep its hooks in you long after the last page is read, and marks the arrival of a tremendously wise and talented writer.""—Ben Fountain Set in 1970-90s Texas, a mesmerizing story about a fierce woman and the partner-in-crime she can't escape, perfect for readers of Where the Crawdads Sing and Valentine. It was 1970 when thirteen-year-old runaway Kit Walker was abducted by Manny Romero, a smooth-talking, low-level criminal, who first coddled her and then groomed her into his partner-in-crime. Before long, Kit and Manny were infamous for their string of gas station robberies throughout Texas, making a name for themselves as the Texaco Twosome. Twenty years after they meet, Kit has scraped together a life for herself and her daughter amongst the pecan trees and muddy creeks of the town of Pecan Hollow, far from Manny. But when he shows up at her doorstep a new man, fresh out of prison, Kit is forced to reckon with the shadows of her past. A gritty, penetrating, and unexpectedly tender novel, Shadows of Pecan Hollow is a hauntingly intimate and distinctly original debut about the complexity of love—both romantic and familial—and the bonds that define us. "Paper Moon meets Badlands in this mesmerizing Texas backroads thriller, a twisty story of a runaway girl who finds a home and a desperate love on the road with an opportunistic criminal."—Janet Fitch